Radiation therapy in locally advanced non-small-cell lung cancer: an overview of dose/fractionation strategies to improve outcomes. (October 2012) - Filippi, Andrea Riccardo; Mantovani, Cristina; Ricardi, Umberto
SUMMARY Local disease control and survival rates of locally advanced non-small-cell lung cancer patients are still poor, even with the best combination of chemotherapy and radiotherapy. Radiotherapy dose is believed to play a major role in controlling local disease, due a steep dose–response relationship for lung cancer, and therefore there is a strong biological rationale to escalate/accelerate the dose. In previous years, several prospective trials explored this option and obtained contrasting results, and recent technical advances in radiotherapy raise the issue of which approach should be considered the most appropriate for future studies. In this article, we briefly review selected prospective Phase I–III trials testing escalation/altered fractionation and focus on future perspectives in this field.